Preliminary Assessment of Ozone-Activated Chitosan as An Efficient Adsorbent for Dye Removal - Nadya Alfa Cahaya Imani; Ria Wulansarie; Indrasukma Permanadewi; Maharani Kusumaningrum; Khodijah Muti'ah; Ira Listyaningrum; Fathin Latifah; Fenia Nur Azzahra (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2026)
Chitosan-based adsorbents are promising for wastewater treatment due to their biodegradability and abundant functional groups, but their dense structure and low porosity often limit adsorption performance. This study investigated ozone-assisted modification as a green approach to enhance the surface morphology and adsorption capacity of chitosan films under different pH (6–8), temperatures (30–50°C), and ozonation times (10–30 min). Structural characterization using SEM, optical microscopy, and FTIR showed that ozonation transformed the compact chitosan matrix into a more porous structure. However, excessive ozonation caused structural degradation and fragmentation. FTIR analysis confirmed changes in hydrogen bonding and partial modification of glycosidic linkages without destroying the main chitosan backbone. Adsorption tests using methylene blue (MB) and methyl orange (MO) demonstrated improved dye removal after ozonation, with sample 651 achieving the highest efficiencies of 47.06% for MB and 61.02% for MO. Acidic ozonation conditions produced the best performance, while prolonged treatment reduced adsorption due to excessive depolymerization and loss of active sites. Overall, controlled ozonation effectively improved the physicochemical properties and adsorption potential of chitosan for the treatment of dye-contaminated wastewater.